Tuber rufum from Ŕo Negro, Argentina, with notes on Spegazzini’s Tuberales - Romero, Andrea Irene (2001)
Knowledge about the Tuberaceae of Argentina is very poor. Spegazzini (1887) made the first records describing two species belonging to this group in amore general work with five hypogeous fungi. These t wo species have received no further attention. Although there is not a complete study of the Ar gentine Tuberales, Crespo and Dominguez de Toledo (1994) have recently reported Tuber separans Gilkey, from the province of Cordoba. More recently, Crespo (1996, pers. comm.) observed T. maculatum Vitt. and T. shearii Harkn. from the same province, and Lorenzo & Calvelo (2000) reported Tube r maculatum. from Patagonia. Almost simultaneously, another truffle was found in a fruit farm from this area, associated with Tilia sp. and Quercus sp., both of which are introduced deciduous trees, during autumn. It has been identified as Tuber rufuni Pico, This paper describes this new record for Argentina and makes some comments on Spegazzini´s type material.